Граница: [роман] / Роберт Маккаммон - Маккаммон Роберт Рик (thebigbook, 2021)
Экземпляры: Камская библиотека (20220629) / Инвентарный номер: 15681 / Цена: / Сис.шифр: 84(7Сое)-445.1 / Авт.знак: М 15 / ББК: 84(7Сое)-445.1